Effects of nine months resistance training on cycling economy in elderly men and women - Fernández Lezaun, Elena (2016)
The aging process, along with the lifestyle, is associated with loses in functional capacity and independence due to factors such as decreases in muscle mass, strength, and aerobic capacity, among others. Resistance training (RT) has been shown to induce strength and muscle size gains in the elderly. Improvements in maximal endurance capacity have been shown in some studies, while others have found no change. The purpose of the present study was to examine the effects of RT on the cycling economy in the elderly.